Archival process modeling for Arkib UiTM by adopting open archive information system reference model / Raja Azzam Raja Aznor - Raja Aznor, Raja Azzam (2011)
A framework for archival system is important for the understanding and increasing awareness of archival concepts, which is needed for long term digital information preservation and access. The aim for this research project is to propose archival process model for Arkib UiTM by adopting Open Archive Information System (OAIS) Reference Model. Currently Arkib UiTM is not using any archiving model to managing their archiving process. The objectives of this project are to describe Functional Model of Open Archive Information System (OAIS), to map requirements on OAIS functional entities for archival process modeling, and to validate requirement through prototyping. The methods that used in this project are problem identification and planning, requirement gathering, analysis, and design. The finding result shows the validated prototype which include the mapped requirements with adopted the OAIS Functional Model for Arkib UiTM's archival process model. With the design of archival process modeling, it will help to understand the entities involve and overall workflow of archival process for Arkib UiTM especially in preserves digital information and access.